Paraquat lung – a rare cause of diffuse parenchymal lung disease: Paraquat lung - Agarwal, Mehul; Gupta, Manohar Lal; Deokar, Kunal; Bharti, Neha; Jain, Priyank (Acta Biomedica Atenei Parmensis, 2021)
.